Picrosirius‐Polarization Method for Collagen Fiber Detection in Tendons: A Mini‐Review - Jie Liu; Ming‐you Xu; Jing Wu; Hao Zhang; Li Yang; Deng‐xing Lun; Yong‐cheng Hu; Bin Liu (Orthopaedic Surgery, 2021)
Although the structure and composition of collagen have been studied by polarized light microscopy since the early 19th century, many studies and reviews have paid little or no attention to the morphological problems of histopathological diagnosis. The morphology of collagen fibers is critical in guiding mechanical and biological properties in both normal and pathological tendons. Highlighting the organization and spatial distribution of tendon‐containing collagen fibers can be very useful for visualizing a tendon's ultrastructure, biochemical and indirect mechanical properties, which benefits other researchers and clinicians. Picrosirius red (PSR) staining, relying on the birefringence of collagen fibers, is one of the best understood histochemical methods that can highly and specifically underline fibers better than other common staining techniques when combined with polarized light microscopy (PLM). Polarized light microscopy provides complementary information about collagen fibers, such as orientation, type and spatial distribution, which is important for a comprehensive assessment of collagen alteration in a tendon. Here, this brief review serves as a simplistic and important primer to research developments in which differential staining of collagen types by the Picrosirius‐polarization method is increasing in diverse studies of the medical field, mainly in the assessment of the morphology, spatial distribution, and content of collagen in tendons.